Investigation on the quantitative analysis and upgrading of recycled plastic composites and blends - Wang, Bin (2021)
The use of recycled plastics is economical and environmentally friendly. However, without scientific classification and quality control systems, the potential value of recycled plastics will be limited. This thesis aims at providing an analysis of the classification technique, modification options, and process optimization for quality improvement and control of recycled polymer composites and blends. Laboratory evaluation of the infrared (IR) spectroscopy on the quantitative analysis of polymer composites made from polypropylene (PP) and talc was performed. Attenuated total reflectance (ATR) accessory was used for the quantification due to its advantages of rapid analysis and no sample preparation. Due to the short penetration depth (0.5-3 μm) of IR beam from the ATR, the influence of talc homogeneity in PP on the accuracy of quantitative analysis has been discussed. Through four-time multiple extrusions of PP/talc composites, a more accurate calibration was established with the coefficient of determination (R2) increased from 0.910 to 0.996 compared to the single-time extruded calibration. Based on the calibration results, the prediction was made on compositional analysis of PP/talc composites waste from the automobile industry. Mechanical properties of obtained recycled composites were evaluated and controlled according to the compositional information. Correlations were found between the composition and mechanical properties of recycled PP/talc, which indicates the potential of IR quantitative analysis on the quality control of polymer composites waste. Upgrading polymer blends of PP and PET (polyethylene terephthalate) through compatibilization was evaluated in terms of morphological and mechanical properties.